PENGARUH BERBAGAI JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN SEMAI NYATOH (Palaquium sp.) - Fitriana, Fitriana; Umar, Husain; Irmasari, Irmasari (Universitas Tadulako, 2015)
Manure is an organic substance used as an organic fertilizer in agriculture. This research aimed to know the effect of manure on seedling growth of Nyatoh ( Palaquium sp). This research took place at the Seedbed of Forestry Faculty of Tadulako. It was conducted for three months from April to June 2013. This research used Completely Randomized Design (CRD), which consists of four treatments, namely : M0 = soil without manure application (Control), M1 = soil + cow manure (1:1), M2 = soil + chicken manure (1:1), M3 = soil + goat manure (1:1), Each treatment was performed repeatedly for ten times so that the total samples were forty. These results indicated that the increase was in average height, M0 = 20 cm , M1 = 20.7 = 20.6 cm M2 , and M3 = 20.8 cm ; increase in mean diameter, M0 = 0.08 mm , 0.14 mm = M1 , M3 = 0.18 mm , and the increase in the average number of leaves , M0 = 5.5 strands , strands of M1 = 6.3 , M2 = 5.8 strands , and M3 = 6.6 strands . Keywords: Manure, Growth, Palaquium sp.